Using the Job Demands-Resources Model to Underpin the Pandemic Nurses’ Turnover Intention Model to Examine Nurse Turnover Intentions in The Bahamas During the COVID-19 Pandemic: A Theory Paper - Rolle Sands, Shamel Yvonne; Covell, Christine; Caine, Vera (International Journal of Bahamian Studies, 2022)
Nurse turnover can affect the accessibility of healthcare services, quality of patient care, and nurse well-being. Various individual and contextual factors have been found to predict nurse turnover. A growing body of evidence now suggests the emergence of another potential predictor─fear related to the novel coronavirus, SARS-CoV-2 also known as COVID-19. To limit consequences, stakeholders must collaboratively develop empirically supported interventions to reduce nurse turnover. The purpose of this paper is to explain the novel use of the Job Demands-Resources (JD-R) model as a theoretical underpinning of the empirically supported Pandemic Nurses’ Turnover Intention (PNTI) model which is used to examine factors influencing nurses’ turnover intentions in The Bahamas during the COVID-19 pandemic.